Magnesium alloys based on the Mg–Al– Mn–Ca system, additionally alloyed with Zr and La for high‑speed deformation of products and semi‑finished products - A. T. Volochko; V. A. Zelenin; M. S. Kovalko; D. S. Fedorovich; Wang Cheng (Литьë и металлургия)
The article presents calculations and analysis of phase equilibria in magnesium alloys of the Mg–Al–Mn–Ca system with additional alloying of Zr and La. An assessment of the influence of the degree, deformation rate, and extrusion temperature on the composition, structure, and mechanical properties of the material has been evaluated. The impact of heat treatment of deformed samples on the complex of strength and plastic properties has been investigated.